From Advice to Action: How Finfluencers are Reshaping Investment Behavior - Khoirotunnisa, Fani (Journal of Economics, Business, and Government Challenges, 2024)
This study explores the role of financial influencers (finfluencers) in shaping personal finance and investment behaviors, with a focus on gendered communication strategies. As social media platforms become key sources of financial advice, finfluencers have expanded access to financial information, reaching wider audiences. The study reveals that men emphasize data-driven, quantitative aspects of investing, while women often use narrative-based approaches, reflecting gendered norms in financial advice. While finfluencers contribute positively to financial literacy, the study also identifies biases and stereotypes that influence how advice is perceived and acted upon. By analyzing finfluencer content, the study shows how they reshape financial subjectivities—how individuals think, feel, and act regarding finances. The findings suggest that while finfluencers increase financial participation, they also reinforce biases, posing challenges for equitable financial education. The study calls for further research and regulatory measures to address these issues and better understand the long-term effects of finfluencers on financial behaviors.